Nutrient Dynamics During Flood Events in Tropical Catchments: A Case Study in Southern Vietnam. Issue 5 (7th May 2014) - Quan, Nguyen Hong; Meon, Günter
<x xml:space="preserve">Abstract</x> Assessing surface water quality variation as well as chasing water pollution sources is essential for water quality management. However, for existing conditions in developing countries, this assessment may not be done properly in many affected catchments due to limited data and lacking of tools. In particular, pollutant transport from the catchment to its river system during flood events needs quantification and is the aim of the study. For this, a combined water quality monitoring and modeling approach is proposed. The study was exemplarily performed for a typical ungauged medium scale catchment located in the southern area of Vietnam. The available budget allowed at least a limited monitoring of nutrients and driven parameters (e.g., flow, sediment). These data were used to, in total, successfully calibrate the complex Hydrological Simulation Program‐Fortran (HSPF) model. The results lead to three main conclusions: (1) the contributions of point and diffuse sources to nutrient loadings could clearly be identified with the help of monitoring; (2) water quality sampling during flood events is critical to assess pollution sources, especially, diffuse ones. However, just a monitoring of data alone is not adequate to interpret the observed concentrations; modeling is required. (3) Despite of the limited amount of data, which could be recorded and processed during the study, a representative catchment modeling during floods could be performed. It delivered essential information for linking pollution sources with water quality data. Furthermore, the limits of an application of the complex HSPF model under given conditions were shown.